Online characterization of ambient temperature influence on die swell behavior of rubber compound. (December 2022) - Du, Zhongjin; Ziegmann, Gerhard; Zhao, Hongying; Zhao, Shugao
Abstract: In this study, the influence of the ambient temperature in the range of 20–60 °C on the die swell behavior of rubber compound were studied by a capillary rheometer with new designed external heating device. The results demonstrated that the die swell ratio (B) increased rapidly in the initial phase and reached a stable value after a certain time. The time dependence of B was then calculated based on the experimental data using Burger's model. In addition, it can be found that B was proportional to the ambient temperature of the extrudate, since the relaxation time decreased obviously with increasing ambient temperature. At the constant time of 130 min, B in the range of 20–60 °C were 1.393, 1.405, 1.420, 1.425 and 1.438 mm, respectively. Furthermore, an equation was established to describe the relationship among the B, test time and ambient temperature. The calculated value was consistent with experimental data, which was 1.447 and 1.449 mm, respectively. While the equation was not applicable when the ambient temperature lay above 70 °C due to the decreased interaction between rubber and carbon black. It was also found that the contraction effect played a significant role on the behavior of die swell. B of the extrudate under 60 °C and 70 °C was reduced by 1.5% and 1.2%, respectively. Highlights: The die swell behavior of the rubber compound at different ambient temperature was monitored by online method. With increasing test time, die swell ratio of the extrudate increased rapidly in the initial phase and then kept stable. An equation was established to describe the relationship among the die swell ratio, test time and ambient temperature.